Determination of thermophysical properties of oil-acetone miscella based on the peng-robinson equation of state - E. P. Koshevoy; S. E. Koshevaya; A. G. Vereshchagin; A. A. Skhalyakhov (Новые технологии, 2017)
The article is devoted to the determination of thermophysical properties of oil-acetone miscella based on the Peng-Robinson equation of state. The data of the thermophysical properties of the oil-acetone miscella allow to simulate processes of separation of oil-acetone miscella in extraction technology.